Microstructure Formation and Fracturing Characteristics of Grey Cast Iron Repaired Using Laser. (16th June 2014) - Yi, Peng; Xu, Pengyun; Fan, Changfeng; Yang, Guanghui; Liu, Dan; Shi, Yongjun
Abstract : The repairing technology based on laser rapid fusion is becoming an important tool for fixing grey cast iron equipment efficiently. A laser repairing protocol was developed using Fe-based alloy powders as material. The microstructure and fracturing feature of the repaired zone (RZ) were analyzed. The results showed that regionally organized RZ with good density and reliable metallurgical bond can be achieved by laser repairing. At the bottom of RZ, dendrites existed in similar direction and extended to the secondary RZ, making the grains grow extensively with inheritance with isometric grains closer to the surface substrate. The strength of the grey cast iron base material was maintained by laser repairing. The base material and RZ were combined with robust strength and fracture resistance. The prevention and deflection of cracking process were analyzed using a cracking process model and showed that the overall crack toughness of the materials increased.